Potential Development of Green Chemistry Teaching Materials Based on Environmental and Sustainability Issues - Hamdil Mukhlishin; Rizmahardian Ashari Kurniawan; Rahmat (Postgraduate, University of Mataram, 2025)
This study aims to explore the potential development of green chemistry-based teaching materials integrated with local environmental and sustainability issues in West Kalimantan Province for students of the Chemistry Education Study Program, Universitas Muhammadiyah Pontianak (UMP). The research adopts a descriptive-qualitative approach focusing on the identification of curriculum opportunities, environmental context, and green chemistry principles implementation aligned with Education for Sustainable Development (ESD) and Outcome-Based Education (OBE). Data were collected through document analysis (curriculum review, environmental reports), interviews with lecturers and students, and literature analysis of regional environmental challenges. The results indicate that the local environmental issues (peatland degradation, river pollution, and plastic waste) are relevant to be integrated into chemistry teaching materials. Furthermore, 82.2% of lecturers and 88.6% of students express the need for context-based green chemistry materials emphasizing sustainable local resources. The study concludes that UMP’s chemistry curriculum holds strong potential to develop innovative, environmentally contextualized teaching materials promoting sustainability literacy among students.